A graphic design student's guide to freelance : practice makes perfect - Hannam, Ben (Wiley, 2013)
A Graphic Design Student's Guide to Freelance: Practice Makes Perfect helps graphic design students freelance while in college in order to contextualize the material they are learning in their graphic design classes. In doing so, the material in the text assists graphic design students in rounding out and refining their overall education